Spinal meningiomas: evaluation of 41 patients - (:unkn) unknown (My University, 2005)
AIM: Spinal meningiomas are relatively frequent intraspinal tumors. They constitute 25-46% of all primary spinal neoplasms. METHODS: Forty-one patients with spinal meningiomas surgically treated between 1986 and 2001 are reviewed in this report. There were 32 females and 9 males, aged 16 to 73 years old. Tumor location was cervical in 7 cases and thoracic in 34 cases. All tumors were intradural. All of the patients were operated by laminectomy in prone position. RESULTS: Total excision was achieved in 40 (98%) patients and subtotal excision in 1(2%). The majority of the tumors were meningothelial (42%) or psammomatous (25%). There was no surgical mortality. Four patients (10%) suffered from morbidity: One patient with CSF fistula, 1 deep venous thrombosis, 1 case with paraparesis and 1 wound infection was seen. Neither multiple meningiomas nor malign meningiomas were seen in our series. CONCLUSIONS: Spinal meningiomas are benign tumors and should be excised totally. If the preoperative neurological status is not complicated, fairly good outcome can be achieved.
Keywords: Adult; Female; Humans; Middle Aged; Treatment Outcome; Aged; Adolescent; Male; Spinal Cord Neoplasms; Meningioma